2006
DOI: 10.1007/s10334-006-0059-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging at 1.5 T with immunospecific contrast agent in vitro and in vivo in a xenotransplant model

Abstract: MRI at 1.5 T is able to detect USPIO-antibody conjugates targeting a tumor-associated antigen in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…When reaching r 2 /r 1 close to unity, brightening is observed and can be clearly shown in T 1 -weighted images [4,5]. Adequately capped with biocompatible molecules, fine USPIOs can therefore provide positive contrast (T 1 ) and high signal intensities, which can be valuable assets for vascular imaging [5][6][7], cell tracking [8]and also molecular targeting studies [9]. The signal intensity on T 1 -weighted images of contrast agent solutions obtained by spinecho MR sequences can be estimated by using both r 1 (1/ T 1 ) and r 2 (1/ T 2 ), according to the following equation [10]:…”
Section: Introductionmentioning
confidence: 99%
“…When reaching r 2 /r 1 close to unity, brightening is observed and can be clearly shown in T 1 -weighted images [4,5]. Adequately capped with biocompatible molecules, fine USPIOs can therefore provide positive contrast (T 1 ) and high signal intensities, which can be valuable assets for vascular imaging [5][6][7], cell tracking [8]and also molecular targeting studies [9]. The signal intensity on T 1 -weighted images of contrast agent solutions obtained by spinecho MR sequences can be estimated by using both r 1 (1/ T 1 ) and r 2 (1/ T 2 ), according to the following equation [10]:…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other studies for antibody-functionalized iron nanoparticles, our data suggested that the novel USPIO-CD133 Ab could differentially bind and have the potential to serve as a targeted contrast agent in CSC detection and monitoring by MRI ( Figure 5). [24][25][26][27]53 Consistent with the study regarding to in vivo detection of c-Met expression in rat hepatocarcinogenesis model, intravenous injection of USPIO-CD133 Ab successfully targets and labels the tumor cells in rat tumor models. 58 Studies have shown that polymer-coated nanoparticles, such as USPIO used in the present study, have no or minimal impact on cell viability, proliferation, ROS formation, apoptosis rate, and function, and that they have low toxicity in the majority of cells studied.…”
mentioning
confidence: 84%
“…Precise targeting is based on the use of specific ligands (antibodies, peptides, polysaccharides, and drugs), and this approach can be used in the design of ligand-directed, site-specific contrast accumulating agents and other targeted therapies. [23][24][25][26][27][28][29] By labeling CSCs with SPIO/USPIO, the CSC can be identified and tracked in vivo using an MRI scanner, a reliable anatomical and functional assessment of tumor-bearing animals. 30 With the help of SPIO/USPIO-labeling techniques, more studies identifying and characterizing CSCs as well as developing therapeutic treatments can be accomplished.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…56 Lymphoma cells from >90% of patients with B cell non-Hodgkin's lymphoma (NHL) express this kind of antigen. Importantly, Baio et al 57 used this characteristic of NHL to show the successful use of a commercially available USPIO-anti-CD20 MAb conjugate for MRI imaging in a murine xenotransplant model.…”
Section: Using Spion In Cancer Imaging Applicationsmentioning
confidence: 99%